Preparation method of novel acid and alkali resistant organic tubular nanofiltration membrane
Polysulfonamide tube nanofiltration membrane was prepared through interfacial polymerization, and the modification of glutaraldehyde and polyethylene glycol was solved, which solved the problems of poor tolerance of existing nanofiltration membranes, uneven flow channels and easy damage to the membrane layer in acid and alkali environments, and achieved efficient and stable membrane separation performance and improved production efficiency.
Patent Information
- Application Number
- CN202510000219.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-25
AI Technical Summary
The existing organic tubular nanofiltration membrane has poor tolerance in acid and alkali environments, uneven flow channels, easy to break, and low production efficiency.
Polysulfonamide tube nanofiltration membrane was prepared by interfacial polymerization, and the chemical stability and mechanical properties of the membrane were enhanced by modification of glutaraldehyde and polyethylene glycol, while optimizing the membrane structure and production process.
It significantly improves the acid and alkali resistance of the nanofiltration membrane, solves the problems of uneven flow channels and easy damage to the membrane layer, and improves production efficiency, and is suitable for membrane separation applications with high operating pressure.
Abstract
Description
Technical Field
[0001] The invention relates to the field of separation membrane preparation, and in particular to a method for preparing a novel acid- and alkali-resistant organic tubular nanofiltration membrane. Background Art
[0002] With the continuous development of membrane separation technology, organic tubular nanofiltration membranes have attracted much attention due to their unique separation performance and wide application fields. However, there are still some problems to be solved in the preparation and application of organic tubular nanofiltration membranes in the prior art.
[0003] Chemical stability is one of the key indicators for evaluating the performance of nanofiltration membranes. Unfortunately, traditional nanofiltration membrane materials often show weak tolerance in acidic and alkaline environments. This is mainly because specific chemical bonds in the membrane materials (such as C=O bonds) are easily corroded by acids and alkalis, which in turn damages the overall structure and performance of the membrane and severely shortens the service life of the membrane.
[0004] The membrane preparation process is related to the internal structure of the membrane. At present, the problem of uneven flow channels is common in the preparation process of tubular nanofiltration membranes. The root cause is that the preparation process of the membrane support layer is not optimized enough, which not only affects the separation efficiency of the membrane, but also reduces the stability of the membrane. At the same time, the fragility of the membrane layer is also a technical problem that needs to be overcome urgently. This is mainly because the mechanical strength of the membrane material is insufficient and it is difficult to maintain the integrity of the structure under high operating pressure.
[0005] In addition, low production efficiency is also a key factor restricting the popularization and application of tubular nanofiltration membrane technology. The traditional preparation process is complicated and time-consuming, resulting in high production costs and difficulty in meeting the needs of large-scale production, thus limiting the market potential of this technology. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a novel acid- and alkali-resistant organic tubular nanofiltration membrane. The organic tubular nanofiltration membrane prepared by the method not only has excellent acid- and alkali-resistant performance, but also solves the problems of uneven flow channel, easy damage of the membrane layer, and low production efficiency in the prior art.
[0007] The method for preparing a novel acid- and alkali-resistant organic tubular nanofiltration membrane of the present invention comprises the following steps: S1 Preparation of casting solution: mixing, stirring, dissolving, filtering and degassing the polymer material, additives and solvent to obtain the casting solution; S2 non-woven fabric pretreatment: cut the double-layer non-woven fabric into long strips, and use hot air to blow the surface of the non-woven fabric for later use; S3 film coating and tube winding: the casting liquid is evenly coated on the surface of the non-woven fabric by centrifugal spraying through a pump, and the coated non-woven fabric is rolled into a tube at 30-70°C to obtain a tubular ultrafiltration membrane; S4 interfacial polymerization reaction: immersing the tubular ultrafiltration membrane into an aqueous phase, removing excess aqueous phase, and then immersing the membrane into an organic phase for interfacial polymerization reaction to obtain a polysulfonamide tubular nanofiltration membrane; S5 modified tubular nanofiltration membrane: The polysulfonamide tubular nanofiltration membrane is first immersed in a solution containing glutaraldehyde (GA), then immersed in a solution containing polyethylene glycol (PEG), and finally washed and dried to obtain the membrane.
[0008] According to the present invention, the polymer material in step S1 is one of polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, polyether sulfone, polysulfone and cellulose acetate.
[0009] According to the present invention, the solvent in step S1 is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0010] According to the present invention, the additive in step S1 is at least one of methanol, ethanol, ethylene glycol, propylene glycol, glycerol, sodium lauryl sulfate, polyvinyl pyrrolidone, polyethylene oxide, polyethylene oxide, polyvinyl alcohol, methyl cellulose, lithium nitrate and lithium chloride.
[0011] According to the present invention, the mass ratio of the polymer material, the additive and the solvent in step S1 is 10-30:1-20:50-89.
[0012] According to the present invention, the stirring rate in step S1 is 100-1000 rpm.
[0013] According to the present invention, the dissolution temperature in step S1 is 50-90° C., and the dissolution time is 12-48 hours.
[0014] According to the present invention, the width of the long strip non-woven fabric in step S2 is 9 to 38 mm.
[0015] According to the present invention, the edge processing butt joint width reserved for each non-woven fabric outer layer in step S2 is 1 to 5 mm.
[0016] According to the present invention, the tube rolling method in step S3 is as follows: firstly, the long strips of non-woven fabric are butt-bonded at their butt joints with an adhesive material, then the butt-bonded joints are sewed, and finally, 1 to 5 mm of the outer layer of the non-woven fabric is reserved for ultrasonic welding.
[0017] Furthermore, the adhesive material is ethylene-vinyl acetate copolymer, polyamide, polyurethane, polyester or polyethylene.
[0018] Furthermore, the ultrasonic welding is continuously performed along the joints of the non-woven fabric strips, the width of the weld of the outer non-woven fabric strip is 1 to 5 mm, the ultrasonic frequency used is 15 to 40 kHz, the amplitude is 10 to 50 µm, and the welding pressure is 3.0 to 8.5 bar.
[0019] According to the present invention, the aqueous phase solution in step S4 is prepared by adding a certain amount of piperazine (PIP), sodium dodecyl sulfate (SDS) and 4-dimethylaminopyridine (DMAP) into water and uniformly dissolving them by ultrasonication.
[0020] Furthermore, the mass concentration of piperazine (PIP) in the aqueous phase solution is 0.1-0.8%. Furthermore, the mass concentration of sodium dodecyl sulfate (SDS) in the aqueous phase solution is 0.01-1%.
[0021] Furthermore, the mass concentration of 4-dimethylaminopyridine (DMAP) in the aqueous phase solution is 0.01-5%.
[0022] According to the present invention, the oil phase solution in step S4 is composed of tris(benzenesulfonyl) chloride (TSC) and a co-solvent.
[0023] Furthermore, the mass ratio of benzenetrisulfonyl chloride (TSC) to the co-solvent in the oil phase solution is 90:10 to 80:20.
[0024] Furthermore, the co-solvent is ketone, alcohol or ether.
[0025] Furthermore, the ketone is acetone, methyl ethyl ketone or cyclohexanone.
[0026] Furthermore, the alcohol is ethanol, methanol or isopropanol.
[0027] Furthermore, the ether is diethyl ether, tetrahydrofuran or dioxane.
[0028] According to the present invention, the immersion time in the aqueous solution in step S4 is 1 to 5 minutes, and the immersion time in the oil solution is 30 seconds to 2 minutes.
[0029] According to the present invention, the mass concentration of glutaraldehyde in step S5 is 0.1% to 0.5%, and the mass concentration of the polyethylene glycol solution is 10% to 50%.
[0030] According to the present invention, the immersion treatment conditions in step S5 are: temperature of 35°C to 45°C, pH=3 to 4, and time of 30min to 60min.
[0031] Compared with the prior art, the present invention has the following technical effects: 1) The polysulfonamide (PSA) prepared by the interfacial polymerization reaction of the present invention has excellent chemical and thermal stability. Compared with the C=O bond of polyamide (PA), the oxygen of the S=O bond of polysulfonamide (PSA) is less susceptible to acid corrosion.
[0032] 2) The tubular nanofiltration membrane of the present invention uses non-woven fabric as the supporting layer, has good mechanical properties, is suitable for membrane separation applications with high operating pressure, and adopts a straight-rolling process of first coating and then edge docking, which solves the problems of uneven flow channels, easy damage of the membrane layer, and low production efficiency in the prior art.
[0033] 3) The present invention chemically modifies the polysulfonamide (PSA) tubular nanofiltration membrane by using polyethylene glycol (PEG) functionalized materials, and uses the aldehyde groups in glutaraldehyde (GA) to react with the unreacted amine groups on the surface of the PSA-based membrane to enhance the cross-linking degree of the active layer, and significantly improves the antifouling performance of the membrane by combining the unreacted aldehyde groups with the hydroxyl groups of PEG. This not only optimizes the structural stability of the membrane, but also effectively improves its durability and cleaning efficiency in practical applications. DETAILED DESCRIPTION
[0034] A method for preparing a novel acid- and alkali-resistant organic tubular nanofiltration membrane comprises the following steps: S1 Preparation of casting solution: mixing, stirring, dissolving, filtering and degassing the polymer material, additives and solvent to obtain the casting solution; S2 non-woven fabric pretreatment: cut the double-layer non-woven fabric into long strips, and use hot air to blow the surface of the non-woven fabric for later use; S3 film coating and tube winding: the casting liquid is evenly coated on the surface of the non-woven fabric by centrifugal spraying through a pump, and the coated non-woven fabric is rolled into a tube at 30-70°C to obtain a tubular ultrafiltration membrane; S4 interfacial polymerization reaction: immersing the tubular ultrafiltration membrane into an aqueous phase, removing excess aqueous phase, and then immersing the membrane into an organic phase for interfacial polymerization reaction to obtain a polysulfonamide tubular nanofiltration membrane; S5 modified tubular nanofiltration membrane: The polysulfonamide tubular nanofiltration membrane is first immersed in a solution containing glutaraldehyde (GA), then immersed in a solution containing polyethylene glycol (PEG), and finally washed and dried to obtain the membrane.
[0035] According to the present invention, the additive in step S1 is at least one of methanol, ethanol, ethylene glycol, propylene glycol, glycerol, sodium lauryl sulfate, polyvinyl pyrrolidone, polyethylene oxide, polyethylene oxide, polyvinyl alcohol, methyl cellulose, lithium nitrate and lithium chloride.
[0036] When the additive is methanol, ethanol, ethylene glycol, propylene glycol or glycerol, it can be used to adjust the polarity of the solvent and the solubility of the polymer material.
[0037] When sodium dodecyl sulfate is selected as an additive, it can be used to reduce the surface tension of the casting solution and promote the uniform distribution of polymer materials.
[0038] When the additive is polyvinyl pyrrolidone, polyoxyethylene, polyethylene oxide or polyvinyl alcohol, it can be used to enhance the stability of the casting solution.
[0039] The additive is methyl cellulose, which can be used to adjust the viscosity of the casting solution to obtain suitable membrane structure and performance.
[0040] When lithium nitrate or lithium chloride is used as an additive, the pore size and distribution of the membrane are regulated by affecting the interaction between polymer chains.
[0041] According to the present invention, the aqueous phase solution in step S4 is prepared by adding a certain amount of piperazine (PIP), sodium dodecyl sulfate (SDS) and 4-dimethylaminopyridine (DMAP) into water and uniformly dissolving them by ultrasonication.
[0042] Furthermore, the mass concentration of piperazine (PIP) in the aqueous phase solution is 0.1-0.8%. Furthermore, the mass concentration of sodium dodecyl sulfate (SDS) in the aqueous phase solution is 0.01-1%.
[0043] Furthermore, the mass concentration of 4-dimethylaminopyridine (DMAP) in the aqueous phase solution is 0.01-5%.
[0044] Furthermore, the amount of water in the aqueous phase solution is determined according to the concentrations and total volume of piperazine, sodium dodecyl sulfate and 4-dimethylaminopyridine (DMAP) components, and ensures that all components can be fully dissolved to form a uniform aqueous phase solution. Example 1
[0045] The mass percentage formula composition is 20 g of polyvinylidene fluoride (PVDF) material and 67 g of N-methylpyrrolidone (NMP), and the mixture is stirred at 50 ° C for 12 hours at a stirring speed of 1000 rpm. After cooling to room temperature, 7 g of methanol, 5 g of sodium dodecyl sulfate (SDS) and 1 g of lithium chloride are added and stirred for 12 hours. After standing and degassing, it is set aside. At the same time, the double-layer non-woven fabric is cut into strips with a width of 15.5 mm. The outer layer of each non-woven fabric is reserved for edge processing and docking with a width of 3 mm for subsequent docking and bonding. Use hot air to blow the surface of the non-woven fabric to remove surface impurities and prepare for coating operation. Next, the prepared casting solution is evenly coated on the surface of the pretreated non-woven fabric by centrifugal spraying using a pump, and then rolled at 50°C to obtain a tubular ultrafiltration membrane with a diameter of 6 mm; specifically, after the long strip of non-woven fabric is bonded with a polyamide adhesive material at the joint, the bonded joint is sutured and reinforced, and then the 3mm edge reserved for the outer layer of the non-woven fabric is fixed by ultrasonic welding, with an ultrasonic frequency of 30 kHz, an amplitude of 30 µm, and a welding pressure of 5.5 bar to ensure that the welding is firm and the sealing is good. The tubular ultrafiltration membrane formed by the above steps is then immersed in an aqueous solution, which is composed of piperazine (PIP), sodium dodecyl sulfate (SDS) and 4-dimethylaminopyridine (DMAP), wherein the mass concentration of piperazine is 0.5%, the mass concentration of sodium dodecyl sulfate is 0.5%, and the mass concentration of 4-dimethylaminopyridine is 2%, and the immersion time is 3 minutes. After removing the excess water phase, the membrane was immersed in an organic phase solution consisting of tris(2-benzenesulfonyl) chloride (TSC) and acetone, with a mass ratio of TSC to acetone of 85:15, and the immersion time was 1 minute. A polysulfonamide (PSA) tubular nanofiltration membrane was formed by interfacial polymerization.
[0046] Finally, the prepared PSA tubular nanofiltration membrane was immersed in a 0.25% glutaraldehyde (GA) aqueous solution at a temperature of 40°C and pH = 3 for 30 minutes. Then, under the same conditions, it was transferred to a 30% polyethylene glycol (PEG) aqueous solution and continued to react for 30 minutes. Finally, the membrane was transferred to deionized water for cleaning and drying to obtain an acid- and alkali-resistant PSA tubular nanofiltration membrane. Example 2
[0047] Mix 15 g of PES material with 73 g of NN dimethylformamide, and stir at 50 ° C at a stirring speed of 500 rpm for 24 hours. After cooling to room temperature, add 5.5 g of ethanol, 4.5 g of polyethylene oxide and 2 g of lithium nitrate and continue stirring for 24 hours. Let it stand for degassing and set aside. At the same time, cut the double-layer non-woven fabric into strips with a width of 9 mm. The outer layer of each non-woven fabric has a reserved edge processing connection width of 1 mm for subsequent docking and bonding. Use hot air to blow the surface of the non-woven fabric to remove surface impurities and prepare for coating operation. Next, the prepared casting solution is evenly coated on the surface of the pretreated non-woven fabric by centrifugal spraying using a pump, and then rolled at 30°C to obtain a tubular ultrafiltration membrane with a diameter of 3 mm; specifically, after the long strip of non-woven fabric is bonded with a polyamide adhesive material at the joint, the bonded joint is sutured and reinforced, and then the 1 mm edge reserved for the outer layer of the non-woven fabric is fixed by ultrasonic welding, with an ultrasonic frequency of 10 kHz, an amplitude of 10 µm, and a welding pressure of 3.0 bar to ensure that the welding is firm and the sealing is good. The tubular ultrafiltration membrane formed by the above steps is then immersed in an aqueous solution, which is composed of piperazine (PIP), sodium dodecyl sulfate (SDS) and 4-dimethylaminopyridine (DMAP), wherein the mass concentration of piperazine is 0.1%, the mass concentration of sodium dodecyl sulfate is 1%, and the mass concentration of 4-dimethylaminopyridine is 2.5%, and the immersion time is 1 minute. After removing the excess water phase, the membrane was immersed in an organic phase solution consisting of tris(2-benzenesulfonyl) chloride (TSC) and methanol, with a mass ratio of TSC to methanol of 90:10, and the immersion time was 30 seconds. A polysulfonamide (PSA) tubular nanofiltration membrane was formed by interfacial polymerization.
[0048] Finally, the prepared PSA tubular nanofiltration membrane was immersed in a 0.1% glutaraldehyde (GA) aqueous solution at a temperature of 45°C and pH = 4 for 60 minutes. Then, under the same conditions, it was transferred to a 50% polyethylene glycol (PEG) aqueous solution and continued to react for 60 minutes. Finally, the membrane was transferred to deionized water for cleaning and drying to obtain an acid- and alkali-resistant PSA tubular nanofiltration membrane. Example 3
[0049] Mix 25 g of PAN material with 65 g of NN dimethylacetamide in a mass percentage formula and stir at 90 ° C at a stirring speed of 100 rpm for 48 hours. After cooling to room temperature, add 1 g of polyvinyl pyrrolidone, 5 g of propylene glycol and 4 g of methyl cellulose and continue stirring for 48 hours. Let it stand for degassing and set aside. At the same time, cut the double-layer non-woven fabric into strips with a width of 38 mm. The outer layer of each non-woven fabric has a reserved edge processing connection width of 5 mm for subsequent docking and bonding. Use hot air to blow the surface of the non-woven fabric to remove surface impurities and prepare for coating operation. Next, the prepared casting solution is evenly coated on the surface of the pretreated non-woven fabric by centrifugal spraying using a pump, and then rolled at 70°C to obtain a tubular ultrafiltration membrane with a diameter of 12.7 mm; specifically, after the long strip of non-woven fabric is bonded with a polyamide adhesive material at the joint, the bonded joint is sutured and reinforced, and then the 5 mm edge reserved for the outer layer of the non-woven fabric is fixed by ultrasonic welding, with an ultrasonic frequency of 40 kHz, an amplitude of 50 µm, and a welding pressure of 8.5 bar to ensure that the welding is firm and the sealing is good. The tubular ultrafiltration membrane formed by the above steps is then immersed in an aqueous solution, which is composed of piperazine (PIP), sodium dodecyl sulfate (SDS) and 4-dimethylaminopyridine (DMAP), wherein the mass concentration of piperazine is 0.8%, the mass concentration of sodium dodecyl sulfate is 0.01%, and the mass concentration of 4-dimethylaminopyridine is 5%, and the immersion time is 2 minutes. After removing the excess water phase, the membrane was immersed in an organic phase solution consisting of benzenetrisulfonyl chloride (TSC) and tetrahydrofuran, with a mass ratio of TSC to tetrahydrofuran of 80:20, and the immersion time was 2 minutes. A polysulfonamide (PSA) tubular nanofiltration membrane was formed by interfacial polymerization.
[0050] Finally, the prepared PSA tubular nanofiltration membrane was immersed in a 0.5% glutaraldehyde (GA) aqueous solution at a temperature of 35°C and pH = 3.5 for 45 minutes. Then, under the same conditions, it was transferred to a 10% polyethylene glycol (PEG) aqueous solution and continued to react for 45 minutes. Finally, the membrane was transferred to deionized water for cleaning and drying to obtain an acid- and alkali-resistant PSA tubular nanofiltration membrane.
Claims
1. A method for preparing a novel acid- and alkali-resistant organic tubular nanofiltration membrane, characterized in that: The steps include: S1 Preparation of casting solution: mixing, stirring, dissolving, filtering and degassing the polymer material, additives and solvent to obtain the casting solution; S2 non-woven fabric pretreatment: cut the double-layer non-woven fabric into long strips, and use hot air to blow the surface of the non-woven fabric for later use; S3 film coating and tube winding: the casting liquid is evenly coated on the surface of the non-woven fabric by centrifugal spraying through a pump, and the coated non-woven fabric is rolled into a tube at 30-70°C to obtain a tubular ultrafiltration membrane; S4 interfacial polymerization reaction: immersing the tubular ultrafiltration membrane into an aqueous phase, removing excess aqueous phase, and then immersing the membrane into an organic phase for interfacial polymerization reaction to obtain a polysulfonamide tubular nanofiltration membrane; S5 modified tubular nanofiltration membrane: the polysulfonamide tubular nanofiltration membrane is first immersed in a solution containing glutaraldehyde, then immersed in a solution containing polyethylene glycol, and finally the membrane is cleaned and dried to obtain the modified tubular nanofiltration membrane.
2. The preparation method according to claim 1, characterized in that: The polymer material in step S1 is one of polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, polyether sulfone, polysulfone and cellulose acetate; the solvent in step S1 is one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; the additive in step S1 is at least one of methanol, ethanol, ethylene glycol, propylene glycol, glycerol, sodium dodecyl sulfate, polyvinyl pyrrolidone, polyoxyethylene, polyethylene oxide, polyvinyl alcohol, methyl cellulose, lithium nitrate and lithium chloride; the mass ratio of the polymer material, additive and solvent in step S1 is 10-30:1-20:50-89; the stirring rate in step S1 is 100-1000rpm; the dissolution temperature in step S1 is 50-90°C, and the dissolution time is 12-48h.
3. The preparation method according to claim 1, characterized in that: The width of the long strip of non-woven fabric in step S2 is 9 to 38 mm; the edge processing and docking width reserved for the outer layer of each non-woven fabric in step S2 is 1 to 5 mm.
4. The preparation method according to claim 1, characterized in that: The method for rolling the tube in step S3 is as follows: firstly, bonding the long strips of non-woven fabric at the joints with an adhesive material, then sewing the joints, and finally ultrasonically welding the outer layer of the non-woven fabric at a reserved position of 1 to 5 mm; Furthermore, the adhesive material is ethylene-vinyl acetate copolymer, polyamide, polyurethane, polyester or polyethylene; the ultrasonic welding is continuously performed along the joints of the non-woven fabric strips, the width of the weld of the outer non-woven fabric strip is 1 to 5 mm, the ultrasonic frequency used is 15 to 40 kHz, the amplitude is 10 to 50 µm, and the welding pressure is 3.0 to 8.5 bar.
5. The preparation method according to claim 1, characterized in that: The aqueous phase solution in step S4 is prepared by adding a certain amount of piperazine, sodium dodecyl sulfate and 4-dimethylaminopyridine into water and uniformly dissolving them by ultrasonication; Furthermore, the mass concentration of piperazine in the aqueous solution is 0.1-0.8%; the mass concentration of sodium dodecyl sulfate in the aqueous solution is 0.01-1%; and the mass concentration of 4-dimethylaminopyridine in the aqueous solution is 0.01-5%.
6. The preparation method according to claim 1, characterized in that: The oil phase solution in step S4 is composed of benzenetrisulfonyl chloride and a co-solvent.
7. The preparation method according to claim 6, characterized in that: The mass ratio of benzenetrisulfonyl chloride to the co-solvent in the oil phase solution is 90:10 to 80:20; Further, the cosolvent is a ketone, an alcohol or an ether; Furthermore, the ketone is acetone, methyl ethyl ketone or cyclohexanone; Furthermore, the alcohol is ethanol, methanol or isopropanol; Furthermore, the ether is diethyl ether, tetrahydrofuran or dioxane.
8. The preparation method according to claim 1, characterized in that: The immersion time in the aqueous solution in step S4 is 1 to 5 minutes, and the immersion time in the oil solution is 30 seconds to 2 minutes.
9. The preparation method according to claim 1, characterized in that: The mass concentration of glutaraldehyde in step S5 is 0.1% to 0.5%, and the mass concentration of the polyethylene glycol solution is 10% to 50%; the immersion treatment conditions in step S5 are: temperature of 35°C to 45°C, pH=3 to 4, and time of 30 min to 60 min.
10. A novel acid- and alkali-resistant organic tubular nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Reverse osmosis membrane post-treatment method and reverse osmosis membrane
CN120771732A
Post-treatment method of reverse osmosis membrane and reverse osmosis membrane
CN120771732B